1993
DOI: 10.1002/aja.1001970102
|View full text |Cite
|
Sign up to set email alerts
|

N‐cadherin mediates sertoli cell‐spermatogenic cell adhesion

Abstract: The complex topological association of Sertoli cells and spermatogenic cells in the testis suggests the existence of cell surface adhesion molecules that regulate cellular interactions within the seminiferous epithelium. The recent report of N-cadherin mRNA expression in the mouse testis implies the involvement of this known adhesion molecule in testicular cell binding. Accordingly, here we report that (1) N-cadherin is found on the surface membranes of rat spermatogenic cells and on Sertoli cells, and (2) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 42 publications
1
53
0
Order By: Relevance
“…Despite its well-established and documented function in various epithelia, the role of the cadherin-catenin complex in the testis still remains elusive. The three basic members of the complex, N-cadherin, a-, and b-catenin are present at the ectoplasmic specialization (Newton et al 1993, Byers et al 1994, Goossens & van Roy 2005. However, the only functional evidence for a direct implication of the complex in spermiogenesis comes from in vitro data: application of an anti-N-cadherin antibody on cultured Sertoli cells, abrogates Sertoli-germ cell interactions (Newton et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Despite its well-established and documented function in various epithelia, the role of the cadherin-catenin complex in the testis still remains elusive. The three basic members of the complex, N-cadherin, a-, and b-catenin are present at the ectoplasmic specialization (Newton et al 1993, Byers et al 1994, Goossens & van Roy 2005. However, the only functional evidence for a direct implication of the complex in spermiogenesis comes from in vitro data: application of an anti-N-cadherin antibody on cultured Sertoli cells, abrogates Sertoli-germ cell interactions (Newton et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, synthetic peptides containing the HAV motif (for example, N-Ac-LRAHAVDING-NH 2 ) have been shown to be capable of inhibiting cadherin-dependent biological processes, such as myoblast fusion (19), neurite outgrowth (8), and embryo compaction (18). Furthermore, antibodies directed against the HAV sequence are also capable of disrupting cadherin-dependent cell adhesion (5,20,21).…”
mentioning
confidence: 99%
“…In this context, synthetic peptides containing the HAV motif (for example, N-Ac-LRAHAVDING-NH 2 ) have been shown to be capable of inhibiting cadherin-dependent biological processes, such as myoblast fusion (19), neurite outgrowth (8), and embryo compaction (18). Furthermore, antibodies directed against the HAV sequence are also capable of disrupting cadherin-dependent cell adhesion (5,20,21).Crystal studies have demonstrated that N-cadherin ECD1 monomers will form two types of dimeric structure, one that might reflect a trans adhesion interface, and one that might reflect the formation of a cis dimer (22). Interestingly, the HAV motif is part of a ␤CFG strand that forms one face of the trans adhesion dimer; however, only the histidine and valine make lattice contacts, and these account for less than 5% of the adhesion interface.…”
mentioning
confidence: 99%
“…In this study, formation of vacuole and shrinkage of the layer of epithelial cells is clearly seen in the control group, but the experimental groups did not show this damage at all or rarely show. This vacuole can result in a loss of cellular connections or reduction of adhesive molecules such as cadherin or loss of generative cells [24]. Peroxidation of poly unsaturated fatty acids of the membrane disturbs the function and permeability of the membrane, resulting in cell destruction and death.…”
Section: Discussionmentioning
confidence: 99%